Movimento estudantil como organização social detentora de projetos políticos - Amon Narciso de Barros (2009)
The organizations considered object of analises and reflexion, in the field of organizational studies are, most of the time, linked to private companies, branches and more recently to those connected to the so called Third Sector, as the NGOs and foundations, which are sometimes also called social organizations due to the understanding that they incorporate the way civil society manifest itself when organized. In this work, we try to call the attention of the researchers in the theory of organizations area to the possibility of adopting the social movements as object of study, as a manifestation of a organization form existing in society and that, having specificities, opens the path for those who are guided by a line of analises focused on social criticism. We aimed at showing that this object has a rationality that can diferentiate itself from that guiding the productive organizations in the capitalist economy,creating space for studies which scape from the imperative of performance that permeates the way the studies in the administration area in general are conducted. In the wide range of social movements (or social organizations) existing in society we chose as object of study thestudent movement practiced in the Universidade Federal de Minas Gerais (UFMG) to exemplify how a civil society organization is constituted around political projects that serve as foundation for the identification of the notion of belonging among the subjects and that make possible the idea of unity in the groups.